-5n+3=33-2n

Simple and best practice solution for -5n+3=33-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5n+3=33-2n equation:


n in (-oo:+oo)

3-5*n = 33-(2*n) // - 33-(2*n)

2*n-5*n-33+3 = 0

-3*n-30 = 0 // + 30

-3*n = 30 // : -3

n = 30/(-3)

n = -10

n = -10

See similar equations:

| -b+6=18+2b | | 7+6k=k-38 | | 5d+7=-6d+73 | | 5+5k=7k+3 | | x-5/5x+20 | | 1/3(9p+6)-(p+1) | | 10-b=4b+10 | | -6w+9=23+w | | -4b-8=-98+6b | | -2+7x=6x+4 | | 8+2w=7w-12 | | -7n+3=-6n+9 | | 3b+1=31+6b | | 4k+1=-8+5k | | -w-9=4w+51 | | -5w-6=w+30 | | -7n+9=-3+5n | | 2m-9=3m+1 | | 6a-8=7a-5 | | 8-4m=-m-4 | | 0.3(4y-8)-3.6y= | | 4(3+4x)-1=59 | | 7w-5=-4w+28 | | 1+2d=-3d+41 | | -1-n=2n-25 | | 7n+1=-n+65 | | 10+6t=3t-17 | | -5t+6=5t-104 | | (9x^2-1)/(3x^2+2x-1) | | 6+b=6b-14 | | 6-2n=n-18 | | -2a+4=-6a+28 |

Equations solver categories